Assessment of hypermucoviscosity as a virulence factor for experimental Klebsiella pneumoniaeinfections: comparative virulence analysis with hypermucoviscosity-negative strain - Yi-Chun Lin; Min Lu; Hui Tang; Hsu-Chung Liu; Ching‐Hsien Chen; Keh-Sen Liu; Chingju Lin; Chien‐Shun Chiou; Ming-Ko Chiang; Chuan‐Mu Chen; Yi‐Chyi Lai (2011)
Abstract Background Klebsiella pneumoniae displaying the hypermucoviscosity (HV) phenotype are considered more virulent than HV-negative strains. Nevertheless, the emergence of tissue-abscesses-associated HV-negative isolates motivated us to re-evaluate the role of HV-phenotype. Results Instead of genetically manipulating the HV-phenotype of K. pneumoniae , we selected two clinically isolated K1 strains, 1112 (HV-positive) and 1084 (HV-negative), to avoid possible interference from defects in the capsule. These well-encapsulated strains with similar genetic backgrounds were used for comparative analysis of bacterial virulence in a pneumoniae or a liver abscess model generated in either naïve or diabetic mice. In the pneumonia model, the HV-positive strain 1112 proliferated to higher loads in the lungs and blood of naïve mice, but was less prone to disseminate into the blood of diabetic mice compared to the HV-negative strain 1084. In the liver abscess model, 1084 was as potent as 1112 in inducing liver abscesses in both the naïve and diabetic mice. The 1084-infected diabetic mice were more inclined to develop bacteremia and had a higher mortality rate than those infected by 1112. A mini-Tn 5 mutant of 1112, isolated due to its loss of HV-phenotype, was avirulent to mice. Conclusion These results indicate that the HV-phenotype is required for the virulence of the clinically isolated HV-positive strain 1112. The superior ability of the HV-negative stain 1084 over 1112 to cause bacteremia in diabetic mice suggests that factors other than the HV phenotype were required for the systemic dissemination of K. pneumoniae in an immunocompromised setting.